The Principle of diversity in journalism - Porto, Mauro (Brazilian journalism research, 2005)
This article discusses a journalistic value that has important consequences for political deliberation: diversity. After identifying the key dimensions of the principle of media diversity, the text presents a case study about Jornal Nacional’s coverage of the 2002 presidential election. The study suggests that, although the campaign coverage was balanced and fair, it did not include a diversity of voices in the controversies about the main theme of the electoral process: the economy. Such lack of diversity restrictedthe range of interpretations to which voters were exposed. In 2002, the process of political deliberation was characterized by a media environment with low levels of diversity in terms of access of voicesand interpretive frames. Based on the notion of public interest, the article concludes by proposing measures to promote media diversity, including the ﬁ elds of content regulation, journalistic norms and the role of civil society.